On ZnO nano particle reinforced PVDF composite materials for 3D printing of biomedical sensors. (December 2020) - Kumar, Ranvijay; Singh, Rupinder; Singh, Mohit; Kumar, Pawan
Abstract: The inherent piezoelectric and biocompatibility behaviour of polyvinylidene difluoride (PVDF) and excellent biocompatibility, thermal and magnetic responses of zinc oxide (ZnO) nano particles made their blends as a good candidate for biosensor 3D printing. In this study, the co-precipitation method has been used to prepare the nano-sized ZnO particles, which are further reinforced with PVDF on twin screw compounder with the controlling proportion of ZnO, forced loading, and torque. The investigations of mechanical, thermal, morphological, and shape memory effect have been performed on the prepared feedstock filaments to check the effect of controlling parameters. It has been observed that maximum mechanical strength (tensile strength, percentage elongation and modulus of toughness) results without ZnO nano particle reinforcement, 1% reinforced critically reduced the mechanical properties but the mechanical properties of 2% ZnO nanoparticle reinforced PVDF composite were obtained better than PVDF-1%ZnO and less than PVDF-0%ZnO. Thermal analysis shows that increase in the ZnO percentage into PVDF improves the normalized heat capacity (25.16 J/g in PVDF to 33.07 J/g in PVDF-2%ZnO). The energy dispersive spectroscopy (EDS) analysis confirms the presence of ZnO on the fracture surface. The shape memory was found 98.22 % for PVDF-2%ZnO at 25 °C.